Soldiers and Politicians Memoirs - Pope, Maurice A. (University of Toronto Press, 2019)
This book was written in the hope that the author's accounts of some of the incidents with which he was directly and indirectly connected during his many years as a member of the Canadian public service might prove of value to students of Canada's military and political history. The author has had the opportunity for a long and careful observation of important periods and episodes in Canada's recent history and his reporting and comment about particular events and in general about the role of Canada in world affairs will be found to be full, thoughtful and fair. There are chapters, for instance, which take up Canada's military unpreparedness in the thirties, the situation in which the country found itself on the outbreak of war, the early days of the Canadian Army in England in 1940-41, Canada's position vis-a-vis the Combined Chiefs of Staff in Washington as this body under Mr.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 26. Nov 2019)
Keywords: BIOGRAPHY & AUTOBIOGRAPHY / Military; Generals -- Correspondence